Integration of the Human Nervous System and Missile Technology in Islamic Education Management - Mukhsin, Mukhsin; Syarofi, Muhammad; Faruq, Dukan Jauhari; Czajkowski, Marek; Dahri, Harapandi (QUALITY, 2025)
Integration of the Human Nervous System and Missile Technology in Islamic Education Management. The nervous system is capable of detecting and transmitting signals as well as providing automatic responses. It is analogous to a missile control system that detects threats and provides automatic responses. From an Islamic perspective, the majesty of human creation can inspire structured and effective education management. This study explores the integration of the nervous system and missile systems as a strategy for fostering adaptive, responsive, and spiritual learners. This study employs a qualitative descriptive approach with a case study design. The informants were the principal of SMP 1 Kencong, the vice principal of curriculum, the Islamic religious education teacher, and the ICT teacher. Data analysis used the Miles and Huberman model, including data reduction, presentation, and drawing conclusions. The results of the study indicate that integrating the principles of the nervous system and missile technology into education promotes adaptive, responsive, and precise learning through the use of Google Classroom, which facilitates quick feedback and personalized learning. This approach not only improves effectiveness but also shapes students’ characters to be independent, responsible, and spiritually valuable.